Accumulation of R&D Capital and Dynamic Firm Performance: A Not-so-fixed Effect Model - Tor Jakob Klette; Frode Johansen (Statistics Norway, Research Department, 1996)
Considering the observed patterns of R&D investment, we argue that a model which allows for a positive feedback from already acquired knowledge to the productiveness of current research, fits the empirical evidence better than the standard model that treats knowledge accumulation symmetrically to the accumulation of physical capital. We present an econometric framework consistent with a positive feedback in the accumulation of R&D capital. The empirical model is econometrically simple and less data-demanding than the standard framework. Our estimates show a significant positive effect of R&D on performance and a positive feedback effect from the stock of knowledge capital. We calculate the depreciation rate and the rate of return to knowledge capital for our alternative framework, and compare our estimated rate of return to results obtained within the standard framework.
Keywords: D24; O30; 330; Productivity; R&D; Knowledge Accumulation; Panel Data.